2022
DOI: 10.4102/ojvr.v89i1.1955
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the minimum inhibitory and mutant prevention concentrations of selected antibiotics against animal isolates of Pasteurella multocida and Salmonella typhimurium

Abstract: Historically, the use of antibiotics was not well regulated in veterinary medicine. The emergence of antibiotic resistance (ABR) in pathogenic bacteria in human and veterinary medicine has driven the need for greater antibiotic stewardship. The preservation of certain antibiotic classes for use exclusively in humans, especially in cases of multidrug resistance, has highlighted the need for veterinarians to reduce its use and redefine dosage regimens of antibiotics to ensure efficacy and guard against the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A number of studies of bacterial isolates from cattle have demonstrated that many types of bacteria are sensitive to florfenicol, in particular, prevalent bacteria that cause respiratory disease in cattle (BRD), namely Mannheimia haemolytica, Pasteurella multocida, Histophilus somni (de Jong et al, 2014;EMA, 2017;Kehrenberg et al, 2004;Plumb, 2004;The United States Pharmacopeial Convention, 2007;Wentzel, 2012), as well as other pathogens such as Bacteroides melaninogenicus and Fusobacterium necrophorum (The United States Pharmacopeial Convention, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies of bacterial isolates from cattle have demonstrated that many types of bacteria are sensitive to florfenicol, in particular, prevalent bacteria that cause respiratory disease in cattle (BRD), namely Mannheimia haemolytica, Pasteurella multocida, Histophilus somni (de Jong et al, 2014;EMA, 2017;Kehrenberg et al, 2004;Plumb, 2004;The United States Pharmacopeial Convention, 2007;Wentzel, 2012), as well as other pathogens such as Bacteroides melaninogenicus and Fusobacterium necrophorum (The United States Pharmacopeial Convention, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, required inocula are prepared via a one-step concentration of the liquid culture. However, they rarely exceed a density of 10 11 CFU/mL ( 9 , 36 , 43 ), usually reaching 10 10 CFU/mL ( 29 , 39 , 44 to 48 ) or 10 9 CFU/mL ( 49 , 50 ). The lower the inoculum density, the more plates are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains isolated from the bovine uterus showed MIC values ≤ 0.25 µg/mL, which was analogous to the results obtained by Liu et al for E. coli strains causing thigh infections in mice [ 58 , 59 ]. For Salmonella strains, the MIC value varied between 0.06 and 0.25 µg/mL [ 60 , 61 ]. Significantly higher MIC values were obtained for Pseudomonas aeruginosa strains, ranging between 1 and 4 mg/mL [ 60 , 62 ].…”
Section: Efficacy Of Enrofloxacin In Veterinary Medicinementioning
confidence: 99%